2008
DOI: 10.1105/tpc.107.057547
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Kinase CORYNE ofArabidopsisTransmits the Stem Cell–Limiting Signal CLAVATA3 Independently of CLAVATA1

Abstract: Stem cells in shoot and floral meristems of Arabidopsis thaliana secrete the signaling peptide CLAVATA3 (CLV3) that restricts stem cell proliferation and promotes differentiation. The CLV3 signaling pathway is proposed to comprise the receptor kinase CLV1 and the receptor-like protein CLV2. We show here that the novel receptor kinase CORYNE (CRN) and CLV2 act together, and in parallel with CLV1, to perceive the CLV3 signal. Mutations in CRN cause stem cell proliferation, similar to clv1, clv2, and clv3 mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
445
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(478 citation statements)
references
References 39 publications
18
445
1
5
Order By: Relevance
“…1a). Detailed Y2H assays showed that the full length BIN2 protein interacts with TDRKD, but not with the kinase domain of CRN, another receptor-like protein functioning in CLE signalling 9,20,21 (Fig. 1a, and Supplementary Fig.…”
Section: Bin2 Interacts With Tdr Cytoplasmic Domain In Y2h Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…1a). Detailed Y2H assays showed that the full length BIN2 protein interacts with TDRKD, but not with the kinase domain of CRN, another receptor-like protein functioning in CLE signalling 9,20,21 (Fig. 1a, and Supplementary Fig.…”
Section: Bin2 Interacts With Tdr Cytoplasmic Domain In Y2h Assaymentioning
confidence: 99%
“…The CLAVATA3 (CLV3)/EMBRYO SURROUNDING REGIONrelated (CLE) family of signalling peptides plays crucial roles in the regulation of stem cell maintenance in the meristems 3 . In the shoot apical meristem of Arabidopsis thaliana, CLV3 peptide secreted from stem cells restricts the expression domain of the WUSCHEL (WUS) homeobox transcription factor gene to the organizing centre via three receptor pathways, CLV1, CLV2-CORYNE (CRN) and RECEPTOR-LIKE PROTEIN KINASE 2 (RPK2) [4][5][6][7][8][9][10] . CLV3-WUS signalling makes a negative feedback loop to maintain the homoeostasis of stem cell population in the shoot apical meristem [11][12][13] .…”
mentioning
confidence: 99%
“…For example, CLV3 and CLE40 are responsible for shoot and root apical meristem maintenance, respectively [9,11,12]. CLV3 is perceived by three different receptors or putative receptors, CLAVA-TA1 (CLV1), CLAVATA 2 (CLV2)-CORYNE (CRN), and RPK2/TOAD2, to limit stem cell size by restricting the expression of a homeodomain transcription factor, WUSCHEL (WUS), via a negative feedback loop [13][14][15][16][17][18]. On the other hand, CLE40 is perceived by its putative receptor complex containing two different RLKs, ARA-BIDOPSIS CRIKLY4 (ACR4) and CLV1, to inhibit the expression of a root version of homeodomain transcription factor, WOX5 [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…7 Genetic approach has demonstrated that these 3 receptor complexes function downstream of CLV3 basically, independently of each other, however, it remains unclear whether they are functionally redundant or each has distinct functions. [6][7][8]15 Previously, we have shown that a synthetic CLV3 peptide, MCLV3 could be a useful tool for investigating downstream components of the CLV signaling pathway. 7,9 Here we report the defects of SAM in a recently identified MCLV3 resistant mutant, pub4, 10 and discuss the possible relationship of its causal gene with the CLV signaling pathway.…”
mentioning
confidence: 99%
“…[1][2][3] CLV2, a receptor-like protein, associates with CORYNE (CRN)/SUPPRESSOR OF LLP1 2 (SOL2), a membrane associated protein pseudo-kinase with a short extracellular domain. [4][5][6] RECEPTOR-LIKE PROTEIN KINASE 2 (RPK2) is another receptor-like kinase that is essential for CLV3 signaling. 7 Genetic approach has demonstrated that these 3 receptor complexes function downstream of CLV3 basically, independently of each other, however, it remains unclear whether they are functionally redundant or each has distinct functions.…”
mentioning
confidence: 99%